The use of induced pluripotent stem cells as a platform for the study of depression - Villafranco, Javier; Martínez-Ramírez, Gabriela; Magaña-Maldonado, Roxana; González-Ruvalcaba, Anna Paola; López-Ornelas, Adolfo; Velasco, Iván; Becerril-Villanueva, Enrique; Pavón, Lenin; Estudillo, Enrique; Pérez-Sánchez, Gilberto (Frontiers in Psychiatry, 2024)
The neurobiological mechanisms underlying major depressive disorder (MDD) remain largely unexplored due to the limited availability of study models in humans. Induced pluripotent stem cells (iPSCs) have overcome multiple limitations of retrospective clinical studies, contributing to a more detailed understanding of the molecular pathways that presumably contribute to the manifestation of depression. Despite the significant progress made by these study models, there are still more formidable challenges that will eventually be addressed by these platforms, as further studies may eventually emerge. This review will examine the most recent advances in the comprehension of depression by using human neurons and non-neuronal cells derived from induced pluripotent stem cells of patients with depression. This study highlights the importance of using these platforms to increase our knowledge of depression and address this psychiatric disorder more efficiently.